An Interleaced-stage AC-DC converter feaseble for SST-based railway traction systems - Honório, Dalton de Araújo (2018)
This work proposes an interleaved - stage ac - dc bidirectional power converter topology feasible to medium - volt age (MV) railway systems. It is based on an arrangement that uses Input - Series - Output - Parallel (ISOP) configuration with identical power modules. There are two types of modules: Type A consists of two interleaved legs employing coupl ed - windings so that it is possible to connect a medium - frequency transformer (MFT), together with a voltage doubler cell, while Type B also uses the two interleaved legs, however with an additional one operating in the grid frequency in order to r eplace th e voltage doubler cell . The topology conception is presented, followed by the adopted control and modulation technique. An estimation of semiconductor losses is also discussed through a comparative analysis by means of simulation results , validat ing the improved performance of the introduced approach if compared with similar solutions. The topology results are obtained through experimental test performed in two prototypes of the proposed topology, considering module type A. The single - module demonstr at es the converter functionalities and performance under both steady - state and dynamic conditions , while the two - module structure demonstrates the same aspects for multi - module configurations . It is then possible to state that good performance in terms of efficiency e ven though the proposed power converter presents higher magnetic component count if compared with similar topology, thus making it suitable to high-power AC-DC machine drive applications. .